2023
DOI: 10.1186/s12885-023-10786-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate quality indices and colorectal cancer risk: a case-control study

Abstract: Background Colorectal cancer (CRC) is the fourth and third most common cancer in Iran and the world, respectively. Carbohydrates can lead to the proliferation of cancer cells, including CRC. The current study aimed to investigate the association between glycemic load (GL), insulin load (IL), glycemic index (GI), insulin index (II), low-carbohydrate diet score (LCDS), and carbohydrate quality index (CQI) with CRC odds. Methods The present case-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, only one small case–control study from Iran (71 CRC cases and 142 controls) has reported associations between higher CQI and lower CRC risk (T3-OR = 0.15; 95% CI: 0.06–0.39), as well as an inverse link between LCDs and CRC incidence (T3-OR = 0.28; 95% CI: 0.10–0.82) [ 11 ]. Our results are partly consistent with this case–control study in terms of the inverse association between CRC incidence and CQI, but differ on the LCDs finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, only one small case–control study from Iran (71 CRC cases and 142 controls) has reported associations between higher CQI and lower CRC risk (T3-OR = 0.15; 95% CI: 0.06–0.39), as well as an inverse link between LCDs and CRC incidence (T3-OR = 0.28; 95% CI: 0.10–0.82) [ 11 ]. Our results are partly consistent with this case–control study in terms of the inverse association between CRC incidence and CQI, but differ on the LCDs finding.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the carbohydrate quality index (CQI) has been developed as a comprehensive measure of carbohydrate quality, incorporating multiple factors like dietary fiber content and glycemic index [ 10 ]. A previous small case–control study in Iranians indicated that higher CQI and LCDs were associated with a reduced CRC risk [ 11 ]. However, it did not assess potential interrelationships between these scores or conduct location-specific CRC risk analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, 142 controls and 71 cases were entered into the analysis. Some details of this study have been published previously [ 24 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…All subjects were required to provide written informed consent before the interview. Details of the current study have been previously published [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%